PEMAKNAAN RASISME DALAM FILM (ANALISIS RESEPSI FILM GREEN BOOK) - vernan Axanta (SOURCE : Jurnal Ilmu Komunikasi, 2020)
As a mass communication media, film can make an impact to the audience such as psychological and social impacts. Green Book is a biographical film with the genre of comedy-drama, and directed by Peter Farrelly. This film tells the relationship of mutualism between talented black pianist Dr.Donald Shirley with his driver as well as bodyguard named Tony Vallelonga. This study uses a descriptive qualitative research method with the Stuart Hall reception analysis approach. Reception analysis considers the audience can be a culture agent that means capable of producing meaning from the various discourses offered by a media. The purpose of this study is to determine the position of the audience according to Stuart Hall's three reading positions in interpreting racism in the green book film. The three positions are dominant hegemony position, negotiation position, and opposition position. This research shows that the reading of the audience towards racism in the Green Book film is interpreted differently. Of the eight scenes selected, the informant's reading position is dominated by the opposition's position. But in some scenes, there are also informants who are in a negotiating position and few who are in a dominant hegemony position.